Charakterystyka kliniczna urazów penetrujących narządu wzroku z obecnością ciała obcego wewnątrz gałki ocznej. Część I. Patogeneza i obraz kliniczny - Obuchowska, Iwona; Napora, Katarzyna; Sidorowicz, Aneta; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Intraocular foreign bodies (IOFBs), are the major cause of penetrating ocular trauma and the most serious problem is the resulting impairment of visual function. In this paper, based on published reports and their clinical experience, authors discuss questions of pathogenesis, epidemiology and clinical features of IOFB injuries. Special attention was paid on primary and secondary complications, which include mechanical lesions of the ocular tissues, metallosis and endophthalmitis.